2017
DOI: 10.1103/physrevb.95.214205
|View full text |Cite
|
Sign up to set email alerts
|

Cotunneling and polaronic effect in granular systems

Abstract: We theoretically study the conductivity in arrays of metallic grains due to the variable-range multiple cotunneling of electrons with short-range (screened) Coulomb interaction. The system is supposed to be coupled to random stray charges in the dielectric matrix that are only loosely bounded to their spatial positions by elastic forces. The flexibility of the stray charges gives rise to a polaronic effect, which leads to the onset of Arrhenius-like conductivity behaviour at low temperatures, replacing convent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Nevertheless, it should be noted that the base current has been changed significantly (3.58 µA for Pd, 6.41 µA for Pd/ZIF‐67, 0.24 µA for Pd/PMMA, and 2.66 µA for Pd/ZIF‐67/PMMA) after coating with ZIF‐67 and/or PMMA, which might be caused by the change of the NC's surrounding medium dielectric function. [ 39,48,49 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it should be noted that the base current has been changed significantly (3.58 µA for Pd, 6.41 µA for Pd/ZIF‐67, 0.24 µA for Pd/PMMA, and 2.66 µA for Pd/ZIF‐67/PMMA) after coating with ZIF‐67 and/or PMMA, which might be caused by the change of the NC's surrounding medium dielectric function. [ 39,48,49 ]…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it should be noted that the base current has been changed significantly (3.58 µA for Pd, 6.41 µA for Pd/ZIF-67, 0.24 µA for Pd/PMMA, and 2.66 µA for Pd/ZIF-67/PMMA) after coating with ZIF-67 and/or PMMA, which might be caused by the change of the NC's surrounding medium dielectric function. [39,48,49] During the hydrogen loading-deloading cyclic tests, Pd/ PMMA exhibited positive successive baseline drift (from 0.24 to 0.37 µA) in each cycle, whereas Pd/ZIF-67 and Pd/ZIF-67/ PMMA exhibited a slight negative baseline shift only in the high-hydrogen-pressure range of >1 kPa. The internal mechanism for the baseline drift after repeated cycles of H 2 loading and deloading is not completely clear, even though this phenomenon has often been reported in other works.…”
Section: Real-time Hydrogen Response and Sensing Kineticsmentioning
confidence: 99%
“…This is supported by the lack of observable-induced features noted in the previous section regarding GIXRD on the current output. This may be due to a polaronic effect [22], whereby thinner films have the ability to undergo lattice distortion, which enables the accommodation of accumulated charge through electron transfer, which a thicker film may not exhibit [23].…”
Section: Electrochemical Performancementioning
confidence: 99%
“…With increasing composition, the average hopping length R H and hopping energy W H decrease significantly indicating the formation of additional localized states due to incorporation of NiO into the KNbO 3 system. Nevertheless, there are few reports dealing with the dependence of hopping conductivity on the dis orderedness of the systems in which the charge is transported via phonon-induced tunneling of electrons between localized states randomly distributed in energy and position [56]. Dinno and Schwartz [57] reported that the ac-electrical conductivity increases progressively with increasing grain size of tellurium thin-films (2D).…”
Section: Frequency and Temperature Dependent Ac-resistivitymentioning
confidence: 99%